(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
this article provided information about the role, features, types of pedagogical abilities in the activities of the teacher. The teacher reflected on how to develop pedagogic abilities and how to deal with students. The great alloma, the opinions of psychologists were analyzed.